Cell Cycle Analysis of Epstein-Barr Virus-Infected Cells following Treatment with Lytic Cycle-Inducing Agents - Rodriguez, Antonio (American Society for Microbiology, 2001)
While Epstein-Barr virus (EBV) latency-associated gene expression is associated with cell cycle progression, the relationship between the EBV lytic program and the cell cycle is less clear. Using four different EBV lytic induction systems, we address the relationship between lytic cycle activation and the cell cycle. In three of these systems, G(0) or G(1) cell growth arrest signaling is observed prior to detection of the EBV immediate-early gene product Zta. In tetradecanoyl phorbol acetate-treated P3HR1 cultures and in 5-iodo-2′-deoxyuridine-treated NPC-KT cultures, cell cycle analysis of Zta-expressing cell populations showed a significant G(1) bias during the early stages of lytic cycle progression. In contrast, treatment of the cell line Akata with anti-immunoglobulin (Ig) results in rapid induction of immediate-early gene expression, and accordingly, activation of the immediate-early gene product Zta precedes significant anti-Ig-induced cell cycle effects. Nevertheless, cell cycle analysis of the Zta-expressing population following anti-Ig treatment shows a bias for cells in G(1), indicating that anti-Ig-mediated induction of Zta occurs more efficiently in cells traversing G(1). Last, although 5-azacytidine treatment of Rael cells results in a G(1) arrest in the total cell population which precedes the induction of Zta, cell cycle analysis of the Zta-expressing population shows a significant bias for cells with an apparent G(2)/M DNA content. This bias may result, in part, from activation of Zta expression following demethylation of the Zta promoter during S-phase. Together, these studies indicate that induction of Zta occurs through several distinct mechanisms, some of which may involve checkpoint signaling.